Surveillance of microcephaly and selected brain anomalies in Argentina: Relationship with Zika virus and other congenital infections - Tellechea, Ana Laura (2018)
Fil: Tellechea, Ana Laura. ANLIS Dr.C.G.Malbrán. Centro Nacional de Genética Médica. Registro Nacional de Anomalías Congénitas; Argentina.